Haemonchus contortus: I. atividade de Pleurotus ostreatus em diferentes estádios biológicos do nematoide; II. potencial do poli (ácido lático-co-ácido glicólico) no nanoencapsulamento de IgY antiH. contortus - Matos, Antonio Francisco Igor Magalhães de (2021)
The production of small ruminants is one of the main sources of income for small and medium farmers in tropical and subtropical regions, mainly in the northeast and south regions of Brazil. Among the health problems that affect animals, parasitic diseases stand out as one of the main factors limiting productivity and regularity in the offer of products and derivatives. Epidemiological data indicate that more than 80% of the parasitic load of small ruminants is made up of the helminth Haemonchus contortus. This parasite has a cosmopolitan distribution and is considered the most pathogenic among gastrointestinal nematodes, as it has a bloodsucking habit. The disease in addition to causing the death of sheep and goats in more severe cases, can reduce production and generate additional costs with the use of antiparasitic agents. Due to the importance of control, the excessive and indiscriminate use of anthelmintic resulted in the selection of multi-resistant nematodes and, consequently, a reduction in the action of the available products. Thus, studies that seek non-chemical control methods are essential. Therefore, this thesis was developed with the objectives of evaluating and improving different alternatives in the control of H. contortus: (1) to evaluate in vitro the ovicidal and larvicidal activity of the aqueous extract of the mushroom Pleurotus ostreatus and in gerbils experimentally infected with H. contortus; (2) to analyse the potential of the poly (lactic acidco- glycolic acid) polymer (PLGA) in different proportions of lactic acid and glycolic acid (50:50, 82:18) in the anti-H. contortus immunoglobulin Y nanoencapsulation in vitro and in vivo release using Wistar rats. We conclude that the aqueous extract of P. ostreatus demonstrated nematocidal effects in low concentrations against eggs and larvae of H. contortus in vitro, however without effects in the in vivo test. Likewise, we demonstrate that PLGA nanospheres have the ability to serve as deposits of IgY antibodies and that nanoparticles can be exploited for the delivery of antibodies. However, in both studies, further evaluations are needed to verify the response of the formulations in the target host.